2022
DOI: 10.1002/1878-0261.13219
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus integration sites and genomic signatures in head and neck squamous cell carcinoma

Abstract: A prevalence of around 26% of human papillomavirus (HPV) in head and neck squamous cell carcinoma (HNSCC) has been previously reported. HPV induced oncogenesis mainly involving E6 and E7 viral oncoproteins. In some cases, HPV viral DNA has been detected to integrate with the host genome and possibly contributes to carcinogenesis by affecting the gene expression. We retrospectively assessed HPV integration sites and signatures in 80 HPV positive patients with HNSCC, by using a double capture‐HPV method followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Consistently, Kamal et al found that patients with HPV integration sites into the MACROD2 gene (introns 5, 6 and 7) [14]. Juliette Mainguené et al reported that the third HPV integration hotspot is MACROD2 (4.1%) in head and neck squamous cell carcinoma, with two patients displaying intragenic HPV integration [24]. MACROD2 is a protein-coding gene located at a fragile site on human chromosome 20.…”
Section: Discussionmentioning
confidence: 84%
“…Consistently, Kamal et al found that patients with HPV integration sites into the MACROD2 gene (introns 5, 6 and 7) [14]. Juliette Mainguené et al reported that the third HPV integration hotspot is MACROD2 (4.1%) in head and neck squamous cell carcinoma, with two patients displaying intragenic HPV integration [24]. MACROD2 is a protein-coding gene located at a fragile site on human chromosome 20.…”
Section: Discussionmentioning
confidence: 84%
“…The ability of HPV integration to alter expression of nearby human genes (within 500 Kb) has been demonstrated in both OPSCC and UCSCC [ 7 , 12 ] with recurrent integration sites identified near genes implicated in cancer such as MYC [ 7 , 50 ], MYB [ 7 ], PVT1 [ 51 , 52 , 53 ], RAD51B [ 50 , 54 ], EMBP1 [ 55 ], CD274/PD-L1 [ 7 , 56 ], and SOX2 [ 7 ]. Our results agree with these prior reports confirming integration in or near these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, differences in search parameters (e.g., 100 vs. 500 KB for nearby gene distance) accounted for expected discrepant results. As mentioned in the Section 1 , developer-based workflows have also been reported for the advancement of viral integration site analysis [ 23 , 24 ]. However, the drawbacks of command-line based, open-source software must be deliberated.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, the accompanying bioinformatics analysis has been lagging in development and implementation. Both manual and developer-based, viral-host mapping workflows, i.e., SearcHPV, and nf-VIF (nextflow-based Virus Insertion Finder) have been reported [ 22 , 23 , 24 ]. However, drawbacks of open-source software must be considered by the inexpert user to include: (1) prerequisite for advanced computational skills, (2) uncertainty of software maintenance and support (“abandonware”), (3) security risk, and (4) prohibition by some governmental institutions [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%